Detection of Polymorphisms in BMP15 and GDF9 Genes and Their Associations with Reproductive Traits in Black Bengal Goat of Bangladesh - Mou, M. A.; Hridoy, M. F. A.; Desha, N. H.; Ahmed, S.; Bhuiyan, M. S. A. (Faculty of Animal Science, IPB University, 2024)
The Bone Morphogenetic Protein 15 (BMP15) and Growth Differentiation Factor 9 (GDF9) genes play important roles in follicular development, ovulation rate, and litter size in goats. This study aimed to investigate polymorphisms (SNP) in the coding sequences of BMP15 and GDF9 genes and to find possible associations between identified polymorphisms and reproductive traits in Bangladesh’s Black Bengal goat (BBG). In total, 85 DNA samples of BBG were utilized for PCR amplification, gene fragments sequencing, and subsequent association studies using a generalized linear model implemented by R software. Sequence analysis revealed three SNPs (g.5875A>G, g.6051G>A, and g.6124C>G) in the exon 2 of the BMP15 gene, having one nonsynonymous mutation (g.6124C>G) that changed amino acid glutamic acid to glutamine (E270Q). Besides, the g.3764C>T polymorphism identified in the GDF9 gene was nonsynonymous in nature, changing the amino acid alanine to valine (A273V). The association analysis revealed that litter size and kidding interval differed significantly (p<0.05) for g.6051G>A and g.6124C>G SNP genotypes of the BMP15 gene in the BBG population. Besides, the combined genotypes derived from three BMP15 polymorphisms also significantly affected average litter size and at the 3rd parity. However, the g.3764C>T SNP genotypes of the GDF9 gene showed significant association with only average service per conception. Taken together, the identified SNPs of BMP15 and GDF9 genes showed potentials that could be used as molecular markers for improving the reproductive traits of BBG.